(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
This article explores the theoretical and practical aspects of pedagogical design based on the cognitive approach in music lessons. It analyzes the essence of cognitive pedagogy, its integration into music education, and the possibilities for enhancing students’ cognitive activities through this approach. The article also discusses the stages of pedagogical design, indicators of effectiveness, and key principles necessary for higher pedagogical education institutions to improve the quality of education.